Any study of defeat should be closely allied to the study of heuristic defection (II) - Michaelsen, Jørgen (Passage - Tidsskrift for litteratur og kritik, 2018)
Jørgen Michaelsen: "Any study of defeat should be closely allied to the study of heuristic defection (II)"